Faktor-faktor yang Mempengaruhi Permintaan Konsumen terhadap Cabai Rawit di Kota Denpasar Provinsi Bali - NI MADE SRI WEGA YANTI; KETUT BUDI SUSRUSA; IDA AYU LISTIADEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Factors Affecting Consumer Demand for Cayenne Pepper in Denpasar City,Bali ProvinceCayenne pepper is one of the national leading commodities that is needed by thecommunity. Denpasar City, which has a high population density and per capita foodexpenditure, is a potential market for cayenne pepper production centers in BaliProvince. Consumer demand for cayenne pepper is sometimes uncertain due to theinfluence of various factors. This study aims to analyze the factors that influenceconsumer demand for cayenne pepper and analyze its demand elasticity in DenpasarCity, Bali Province.This research was carried out in Badung Market, Kreneng Market,Ketapian Market, and Sanglah Marketwhich were determined intentionally. Samplingused accidental sampling technique. The number of samples was determined by quotasampling as many as 50 respondents. This study used the Cobb-Douglas requestfunction which is transformed into multiple linear forms of natural logarithms (ln).Theresults showed that the factors that influence consumer demand for cayenne pepper inDenpasar City, Bali Province were the number of family members and tastes. Priceelasticity at D = 0 (not interested in cayenne pepper) and D = 1 (interested in cayennepepper) shows that the demand for cayenne pepper is perfectly inelastic. Cross elasticityat D = 0 (not interested in cayenne pepper) and D = 1 (interested in cayenne pepper)showed that large red chilies, tomatoes, and shallots are items that were not related tocayenne pepper. Income elasticity at D = 0 (not interested in cayenne pepper) and D = 1(interested in cayenne pepper) indicates that the demand for cayenne pepper wasinelastic to income.